Caracterização do perfil de segurança infeccioso dos anticorpos monoclonais imunossupressores - Silva, Nayara Aparecida De Oliveira [UNIFESP] (2021)
The occurrence of infections is a widely known adverse event for immunosuppressive drugs, including monoclonal antibodies (mAB). However, immunosuppressive therapy is not the only risk factor for the development of infections. The autoimmune disease also increases susceptibility to site-specific infections, which may be enhanced by immunosuppression. Thus, the same immunosuppressive mAB may present differences in the infectious profile for each indication due to the influence of autoimmune disease on the risk of certain infections. Given this scenario, the aim of the study was to evaluate the infectious profile, by indication, of immunosuppressive mABs approved for the treatment of two or more autoimmune diseases. A crosssectional, retrospective case/non-case type study was conducted using data from spontaneous reports of suspected adverse drug events (ADEs) received by the Food and Drug Administration (FDA) through June 2020 via the FDA Adverse Event Reporting System (FAERS). Disproportionality analysis on the chance of reporting was performed from the calculation of Reporting Odds Ratios (ROR) with confidence interval at the 95% level (95% CI) and chi-square test with Yates' correction. Ten mABs were analyzed, being 4 anti-TNF alpha (adalimumab, certolizumab, golimumab, and infliximab), 4 anti-interleukin (ixekizumab, secukinumab, tocilizumab, and ustekinumab), and 2 anti-integrin (natalizumab and vedolizumab). Disproportionality analysis identified increased odds of reporting infectious events that appears to be associated with either the (i) indication alone, as these were infections that had disproportionality to an indication independent of the mAB used - as was the case with Clostridium difficile intestinal infections in patients with inflammatory bowel disease, abscesses in patients with Crohn's disease (CD), cytomegalovirus infection in patients with ulcerative colitis (UC), and osteomyelitis in patients with rheumatoid arthritis (RA); or to (ii) the binomial of indication and mAB use, i.e. infections with disproportionality in the chance of reporting for some indication and for one or more mABs, not all of them - such as increased chance of reporting pneumonia, infectious arthritis, and joint tuberculosis in RA patients on anti-TNF use and sepsis in CD patients on anti-integrins. The conclusion is that autoimmune diseases can modulate the infectious profile, increasing the risk of reporting certain infectious events. Thus, the same mAB may show differences in the profile of infectious ADEs according to the indication of use, and these differences should be taken into consideration when designing risk minimization plans to increase treatment safety.